2015
DOI: 10.1093/toxsci/kfv214
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Patterns Associated With Histopathology in Toxic Liver Fibrosis

Abstract: Toxic industrial chemicals induce liver injury, which is difficult to diagnose without invasive procedures. Identifying indicators of end organ injury can complement exposure-based assays and improve predictive power. A multiplexed approach was used to experimentally evaluate a panel of 67 genes predicted to be associated with the fibrosis pathology by computationally mining DrugMatrix, a publicly available repository of gene microarray data. Five-day oral gavage studies in male Sprague Dawley rats dosed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 125 publications
5
49
0
Order By: Relevance
“…Consistent with a role in collagen biosynthetic maturation, increased PCPE-1 expression is reported to accompany fibrosis onset in animal models of hepatic cirrhosis (Hassoun, et al, 2016, Ippolito, et al, 2016, Ogata, et al, 1997), cardiac fibrosis (Kessler-Icekson, et al, 2006, Yu, et al, 2013), and skeletal muscle fibrosis (Hassoun, et al, 2016); and in human dermal scarring (Wong, et al, 2014). Differences in PCPE-1 expression levels in quiescent versus proliferating smooth muscle cells (Kanaki, et al, 2000), and the induced anchorage-independent growth of cultured fibroblasts in which the PCPE-1 gene has been disrupted (Masuda, et al, 1998), have also suggested a possible role for PCPE-1 in cell proliferation control.…”
Section: Introductionmentioning
confidence: 60%
“…Consistent with a role in collagen biosynthetic maturation, increased PCPE-1 expression is reported to accompany fibrosis onset in animal models of hepatic cirrhosis (Hassoun, et al, 2016, Ippolito, et al, 2016, Ogata, et al, 1997), cardiac fibrosis (Kessler-Icekson, et al, 2006, Yu, et al, 2013), and skeletal muscle fibrosis (Hassoun, et al, 2016); and in human dermal scarring (Wong, et al, 2014). Differences in PCPE-1 expression levels in quiescent versus proliferating smooth muscle cells (Kanaki, et al, 2000), and the induced anchorage-independent growth of cultured fibroblasts in which the PCPE-1 gene has been disrupted (Masuda, et al, 1998), have also suggested a possible role for PCPE-1 in cell proliferation control.…”
Section: Introductionmentioning
confidence: 60%
“…SLC16A3, encoding a monocarboxylate transporter 4 protein, has been shown to be a downstream factor of TSTA3 immune response-mediated metabolism coupling cell cycle to postreplication repair in no-tumor hepatitis/cirrhotic tissues (Wang et al, 2012). PCOLCE (Procollagen C-Endopeptidase Enhancer) has been shown to be the strongest in its correlation with the liver fibrosis phenotype (Ippolito et al, 2016). ZBTB16, also named as PLZF, has previously been shown to be down-regulated in hepatocellular carcinoma, which supports our current study that ZBTB16 was down-regulated in liver cancer specimens compared to non-tumor liver specimens (Hui et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Efforts have been made to investigate the potential of TGx data to supply better information for toxicity assessment than traditional animal toxicology studies (Liu et al, 2011(Liu et al, , 2016Ippolito et al, 2016;Sutherland et al, 2016). Furthermore, TGx has been used to investigate similarities between in vitro and in vivo assay systems and to develop translational biomarkers across the species.…”
Section: Microarray Data Processingmentioning
confidence: 99%